Corn and Soybean Production – 2022 Summary - Gretchen F. Sassenrath; Jane Lingenfelser; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2023)
Soybean and corn varieties were tested in replicated field trials at the Southeast Research and Extension Center in Parsons through the Kansas State University variety testing program. In total, nine corn varieties and three maturity checks were tested. Fourteen full season and ten double-cropped soybean varieties were tested, with three maturity checks. Additionally, sorghum and sunflower varieties were tested. The 2022 summer crop growing season was challenging. High temperatures and low rainfall reduced crop production. Crop production was severely impacted by the hot, dry conditions, both across the state and in the cultivar trials at Parsons. No yield results are available for the variety tests from Parsons.
Keywords: crop variety testing; soybeans; full season; double cropped; corn; southeast Kansas